Kepuasan Hidup Mahasiswa Tahun Pertama: Peran dari Kecenderungan Depresi dan Hubungannya dengan Prestasi Akademik - Diana Permata Sari; Winda Valentia, Magdalena; Dinda Dewi Dewani, Chatarina (Jurnal Online Psikogenesis, 2024)
This study aims to examine whether depressive tendency play a role in the relationship between academic achievement and life satisfaction in first-year college students. The research hypothesis is that depression tendency plays a role in the relationship between academic satisfaction and life satisfaction in first year students. A total of 176 respondents which consisted of 142 women and 24 men with an age range of 17-25 years (Age = 18.07; SD = 1.04) and were active students in the second semester of the Psychology Faculty at Sanata Dharma University. The research measuring tool consists of Semester Achievement Index (IPS) of the respondents in the first semester of study, which was obtained from basic Faculty data. Patient Health Questionnaire-9 (PHQ-9) to measure depression compiled by Kroenke, et al. (2001) which was then compiled in an Indonesian version by Dian, et al. (2022). The Satisfaction With Life Scale (SWLS), which has been translated into Indonesian. The scale was originally created by Diener, et al. (1985) and later reviewed by Pavot and Diener (1993). Multiple Regression Analysis (MRA) was used in the research data analysis. The results showed that depressive tendencies were a significant mediator in the relationship between academic achievement and life satisfaction.